2021
DOI: 10.1186/s13677-021-00255-5
|View full text |Cite|
|
Sign up to set email alerts
|

Severity: a QoS-aware approach to cloud application elasticity

Abstract: While a multitude of cloud vendors exist today offering flexible application hosting services, the application adaptation capabilities provided in terms of autoscaling are rather limited. In most cases, a static adaptation action is used having a fixed scaling response. In the cases that a dynamic adaptation action is provided, this is based on a single scaling variable. We propose Severity, a novel algorithmic approach aiding the adaptation of cloud applications. Based on the input of the DevOps, our approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Defining QoS or SLA for application stack would translate to the need of load balancing to support QoS and SLA targeted load balancing [88,121,135] as intent-based constraints that internally would need to be translated into signals such as target utilization, number of errors per type, adjustment to changing health of servers. Load balancing for long (streaming) and short (request/response) flows discussed in Reference [138] further influence the choice of deployment archetype for a specific type of traffic an application receives.…”
Section: Additional Related Workmentioning
confidence: 99%
“…Defining QoS or SLA for application stack would translate to the need of load balancing to support QoS and SLA targeted load balancing [88,121,135] as intent-based constraints that internally would need to be translated into signals such as target utilization, number of errors per type, adjustment to changing health of servers. Load balancing for long (streaming) and short (request/response) flows discussed in Reference [138] further influence the choice of deployment archetype for a specific type of traffic an application receives.…”
Section: Additional Related Workmentioning
confidence: 99%
“…Following publication of the original article [1], the authors identified an error. This error has been corrected to express more accurately the work of Arkian et al [2].…”
mentioning
confidence: 99%
“…This change should also make the last lines of the fourth paragraph of the Section on Rule-based and controltheoretic adaptation approaches more understandable. 1 The erroneous and corrected text are published in this correction article. The original article has been updated.…”
mentioning
confidence: 99%